Analisis Peran Emosi Dalam Kasus Pembullyan : Tinjauan Melalui Studi Pustaka - Mayra Khalidazia Ahyar; Sabrina Zulfanova Saputri; Selfiana Khoirunnisa; Velda Murdiana (LP3M KH Yazid Karimullah Institute, 2024)
Bullying that often occurs among the community, one of which is adolescents, raises very deep concerns that have an impact on one's behavior. This is inseparable from the role of emotions contained in the bullying perpetrator. Behavior is also included in the important role of the impact of bullying situations. Therefore, one needs to understand an intelligence in managing emotions. This research uses the literature method in obtaining data. Data were obtained through official websites, journals, and books as a complement to this research. The purpose of this study confirms that the importance of the role of emotions in oneself that need to be considered and formed from the beginning of growth so that it can reduce the impact of the influence of how a person behaves and responds to a problem.